Desensitization with Self-Antigen dsDNA Inhibits B and T-cell Functions by Modulating Treg as Regulator Immune System in Pristane-induced Lupus Mice Model - saiful arifin (Stem Cell Research and Development Center, Universitas Airlangga, 2019)
The aim of this study was to develop a novel therapeutic method for improving immune system regulation in SLE using escalating dose self-antigen dsDNA immunotherapy. Methods: Female Balb/c mice were given a single intraperitoneal injection of 0.5 ml pristane.. Starting at 12 weeks after injection,. the mice were evaluated for clinical and serological manifestations. Mice with lupus signs (PIL mice) were divided into four groups; positive control group, PIL A (0.01 μg/ml, 0.1 μg/ml, 1 μg/ml ) EDI dsDNA, PIL B (0.1 μg/ml, 1 μg/ml, 10 μg/ml ) EDI dsDNA, and PIL C(1 μg/ml, 10 μg/ml, 100 μg/ml). EDI dsDNA were administered once every week in consecutively. The doses would increase every week. dsDNA were complexed with the cationic polyethylenimine (PEI) before injection. Samples were analyzed for autoantibodies levels (dsDNA, ANA) and ,TGF-β cytokine from serum using ELISA and T-Reg, mature dendritic cells from spleen using flowcytometry.. Results: Escalating dose antigen spesific immunotherapy with self-antigen dsDNA significantly decreased ANA (p=0.02), anti-dsDNA (p=0.03), dendritic cell mature (p=0.02) compare to positive control, and not significantly decreases Th17 cells (p=0,18) but the result tend to get lower. Desensitization using self-antigen dsDNA was increased T-reg proliferation (p=0.00) and level of TGF-β (p=0.03) significantly compare to positive control. Conclusion: Desensitization using self-antigen dsDNA coupled to PEI was able to modulate T-Reg as a regulator immune respon and inhibit B and T cell functions in lupus mice model.